Mechanical Properties of Epoxy-Based Composite Reinforced with Kenaf, Grewia Serrulatta, Human Hair Fibers - Venugopal, P.; Thanigaivelan, R. (Journal of Scientific Research, 2023)
Composite products (polymer based) finds application in industries such as automobiles, space, home appliances, the navy, and defense. This paper focused on preparing a composite specimen with natural fibers such as kenaf, grewiaserrulatta (grewia), and human hair to replace synthetic fiber. Epoxy resin BA LY 556 (Bisphenol-A) is considered a matrix material. Four specimens are prepared with 195 g of matrix and 105 g of fibers in the weight fraction method. Among 105 g fibers, the grewia fiber of 15 g is fixed constant, and the remaining 90 g of fibers, namely kenaf and human hair, are distributed as 0 g, 22.5 g, 67.5 g, and 90 g, respectively. As per ASTM standards, the mechanical property investigation was conducted, namely tensile, flexural, and impact tests. The result shows that the highest mechanical strength, i.e., tensile, flexural, and impact, are obtained in specimen A which is composed of 195 g matrix, 90 g kenaf, and 15 g grewia. Also, specimen B shows the highest strength in flexural properties, composed of 195 g matrix, 15 g human hair, and 90 g grewia. Additionally, microscopic analyses are conducted to verify the orientation and substrate bonding of fibers in the composites.